Enteric and Infectious Diarrheal Diseases in Yemeni Children Admitted with Complicated severe Malnutrition - المحبشي أنس أحمد حسين; الهلالي محمد فرحان; الشماحي حسن عبد الوهاب; الانسي نهى نسر (Latakia University Journal -Medical Sciences Series, 2020)
The aim of this study was to identify the microbial causes of malnutrition in children less than five years with focusing on the most common pathogenic microorganism that cause diarrhea, and the association between diarrhea and malnutrition. One hundred thirty seven stool samples were collected from malnourished children who are suffering from diarrhea and attending Alsabeen Governmental Hospital specialist for Pediatric in Sana’a city. Most children 24% were (36-27 weeks) age group followed by (9-16 weeks) in rate of 21% and males were higher than females in all age groups. All samples were examined for the presence of Bacteria, Rotavirus, Candida albicans, and Parasites. Results yield that there is association between the risk contracting bacterial, viral and protozoa infection with different sex and age groups. Candida albicans were the most dominant (35.8%) and Escherichia coli O157 was a majority cause of diarrhoeal illness (22.6%) followed by Rotavirus (13%). Amikacine has shown the highest sensitivity against E.coli O157 (96%) followed by levofloxacin (70%) then Nitrofurantion (66.7%), while Ampicillin, Cefixime shown the highest resistance to E.coli O157. Malnourished children kwashiorkor have shown the highest rate of mortality (42.6%), while mortality associated with marasmus in 22(17.9%).